Towards a Scaleable 5G Fronthaul: Analog Radio-over-Fiber and Space Division Multiplexing - Rommel, Simon; Dodane, Delphin; Grivas, Evangelos; Cimoli, Bruno; Bourderionnet, Jerome; Feugnet, Gilles; Morales, Alvaro; Pikasis, Evangelos; Roeloffzen, Chris; van Dijk, Paul; Katsikis, Michail; Ntontin, Konstantinos; et al. (Journal of lightwave technology, 2020)
The introduction of millimeter wave (mm-wave) frequency bands for cellular communications with significantly larger bandwidths compared to their sub-6 GHz counterparts, the resulting densification of network deployments and the introduction of antenna arrays with beamforming result in major increases in fronthaul capacity required for 5G networks. As a result, a radical re-design of the radio access network is required since traditional fronthaul technologies are not scaleable. In this article the use of analog radio-over-fiber (ARoF) is proposed and demonstrated as a viable alternative which, combined with space division multiplexing in the optical distribution network as well as photonic integration of the required transceivers, shows a path to a scaleable fronthaul solution for 5G. The trade-off between digitized and analog fronthaul is discussed and the ARoF architecture proposed by blueSPACE is introduced. Two options for the generation of ARoF two-tone signals for mm-wave generation via optical heterodyning are discussed in detail, including designs for the implementation in photonic integrated circuits as well as measurements of their phase noise performance. The proposed photonic integrated circuit designs include the use of both InP and SiN platforms for ARoF signal generation and optical beamforming respectively, proposing a joint design that allows for true multi-beam transmission from a single antenna array. Phase noise measurements based on laboratory implementations of ARoF generation based on a Mach-Zehnder modulator with suppressed carrier and with an optical phase-locked loop are presented and the suitability of these transmitters is evaluated though phase noise simulations. Finally, the viability of the proposed ARoF fronthaul architecture for the transport of high-bandwidth mm-wave 5G signals is proven with the successful implementation of a real-time transmission link based on an ARoF baseband unit with full real-time processing of extended 5G new radio signals with 800 MHz bandwidth, achieving transmission over 10 km of 7-core single-mode multi-core fiber and 9 m mm-wave wireless at 25.5 GHz with bit error rates below the limit for a 7% overhead hard decision forward error correction.